Implementasi Pendistribusian Dana ZIS melalui Program Rumah Singgah Cariu - Aripin, Anggi Januar; Machendrawaty, Nanih; Herman, Herman (Tadbir: Jurnal Manajemen Dakwah, 2023)
Zakat, infaq and alms have similarities in making a significant contribution to prosperity. The BMT Berkah Mandiri Sejahtera Sharia Financing Savings and Loans Cooperative is an institution that organizes social activities, collects and distributes ZIS funds through the Cariu halfway house program with the aim of empowering orphans and the poor. This study aims to determine the planning and mechanism for distributing ZIS funds through the Cariu halfway house program in empowering orphans and the poor at KSPPS BMT Berkah Mandiri Sejahtera, Cariu Branch, Bogor Regency. This research was conducted using a descriptive method with a qualitative approach. The results of the study show that BMT Berkah Mandiri Sejahtera has implemented the function of implementing the distribution of ZIS funds in accordance with predetermined plans, including carrying out approximate actions, determining goals, programs, procedures and budgets. The mechanism for distributing ZIS funds in the Cariu shelter program is carried out directly by the BMT and assisted by volunteers and has several activities in channeling ZIS funds such as activities in the fields of education, health and charity.